Taylor 空间外固定架在膝内侧间室骨关节炎下肢力线调整中的临床应用 (Zhongguo Xiu Fu Chong Jian Wai Ke Za Zhi, 2020)
OBJECTIVE: To explore the safety and effectiveness of Taylor spatial frame (TSF) in the treatment of medial compartmental osteoarthritis (MCOA) of the knee and the adjustment of the lower extremity force line at the same time. METHODS: The clinical data of 30 patients with MCOA who underwent high tibial osteotomy (HTO) between October 2016 and April 2017 were retrospectively analyzed. According to the different fixation methods, they were divided into external fixation group (TSF external fixation, 16 cases) and internal fixation group (locking steel plate internal fixation, 14 cases). There was no significant difference between the two groups in gender, age, side, disease duration, mechanical femur tibia angle (MFTA), and other general data (P>0.05). The operation time and intraoperative blood loss of the two groups were recorded and compared; MFTA was used to evaluate the recovery of the lower extremity force line at last follow-up; Hospital for Special Surgery (HSS) score was used to evaluate the clinical effecacy before operation and at 2 weeks, 1 month, and 3 months after operation. RESULTS: The operation time and intraoperative blood loss of external fixation group were significantly less than those of internal fixation group (P<0.05). All patients were followed up 9-16 months, with an average of 12 months. There were 2 cases of delayed healing in the internal fixation group and 1 case of delayed healing in the external fixation group, and all healed after symptomatic treatment. All patients in the two groups had no complication such as needle infection, nonunion at osteotomy, osteomyelitis, and so on. At last follow-up, MFTA standard was used to evaluate the recovery of force line. The results of external fixation group were all excellent, while the results of internal fixation group were excellent in 10 cases and good in 4 cases. The difference between the two groups was significant (Z=–2.258,P=0.024). The HSS scores in the two groups were significantly improved at each time point after operation, and gradually improved with time after operation (P<0.05). The HSS score of the external fixation group was significantly higher than that of the internal fixation group (t=2.425, P=0.022) at 3 months after operation; and there was no significant difference between the two groups at other time points (P>0.05). CONCLUSION: TSF has unique advantages in HTO treatment of MCOA patients and correction of lower extremity force line, such as shorter operation time, less bleeding, firm fixation, and less complications. It can accurately adjust the lower extremity force line after operation and has good effectiveness. It is an effective and safe fixation method.